SELECTION AND EVALUATION OF ECONOMIC AND EMISSION REDUCTION BENEFIT OF A MINE ELECTRIFICATION SYSTEM FOR TRANSPORTATION IN DEEP OPENCUT COPPER MINES - Chakraborty, Joyanta
The Paris Agreement's global push for decarbonization has created an urgent need for sustainable energy solutions, driving a shift away from fossil fuels. Copper, among other metals, will play a pivotal role in this transition. As demand for copper rises, miners will be compelled to explore deeper opencut mines. However, these mines pose challenges due to their reliance on traditional fuel-intensive trucks for haulage, resulting in substantial Scope 1 emissions and escalating operational expenses. This study addresses the pressing demand for alternative mine haulage systems that can significantly cut fuel consumption and emissions while ensuring economic viability. Focusing on a Latin American copper mine, referred to as "The Copper Pit" for confidentiality purposes, the research identifies and ranks potential haulage systems based on six critical criteria: capital cost, operating cost, flexibility, safety, technological readiness, and emission reduction potential. Utilizing the Analytical Hierarchy Method (AHP), weightage values are assigned to each criterion based on mine management preferences, resulting in a prioritized ranking table. The analysis highlights Trolley Assist truck haulage as the most promising alternative to traditional diesel-truck mining at The Copper Pit. Computer simulations comparing "with Trolley" and "without Trolley" scenarios demonstrate remarkable savings, with up to an 87% reduction in fuel consumption and associated Scope 1 emissions, leading to an 80% reduction in operating costs. While economic benefits are influenced by diesel and power prices, the carbon tax has a lesser impact. The study suggests conducting a feasibility study for a comprehensive understanding of Trolley Assist operations and a phased implementation strategy to mitigate risks. This research's innovative approach combines AHP, DUNCKER diagrams, and simulation techniques, setting it apart from conventional studies. Despite its lower flexibility and requirement of additional capital compared to conventional truck-shovel operations, implementing Trolley Assist in deep copper mines offers the promise of significantly reduced emissions and operating costs, ensuring the sustainability and profitability of copper mining operations.